The Discovery of Insulin: An Important Milestone in the History of Medicine - Vecchio, Ignazio; Tornali, Cristina; Bragazzi, Nicola Luigi; Martini, Mariano (Frontiers in Endocrinology, 2018)
The discovery of insulin represents an authentic breakthrough, characterized, at the same time, by contrasts, controversies and disputes among scholars, as well as by great disappointments, failures and hopes. It is the story of famous, almost famous and little known people, of serendipities, discoveries and re-discoveries. The discovery of insulin has been a milestone and has truly revolutionized both the therapy and the prognosis of the diabetes, one of the diseases most studied in the history of medicine, whose first mentions trace back to a collection of ancient Egyptian, Indian and Chinese textbooks. As stated by Colwell, the introduction of insulin has heralded the end of the so-called “pre-insulin era” or “frustration era”, paving the way for a new era and clinical advancements. The current review offers a broad, comprehensive overview of main steps culminating into insulin discovery, including recent advancements such as personalized and individualized insulin therapy.